2012
DOI: 10.1111/j.1523-1739.2012.01869.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Airborne Lidar System to Model Plant Species Composition and Diversity of Mediterranean Oak Forests

Abstract: Airborne lidar is a remote-sensing tool of increasing importance in ecological and conservation research due to its ability to characterize three-dimensional vegetation structure. If different aspects of plant species diversity and composition can be related to vegetation structure, landscape-level assessments of plant communities may be possible. We examined this possibility for Mediterranean oak forests in southern Portugal, which are rich in biological diversity but also threatened. We compared data from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…Other studies obtained better biodiversity predictions (R 2 > 0.73) under tropical conditions by considering the Shannon index as a dependent variable [43,44]. Under Mediterranean conditions, similar predictions to those obtained in our study were obtained by Simonson et al [45] and Bacaro et al [46] by using the Shannon index and richness, respectively. In another context, Camathias et al [41] obtained lower richness prediction accuracies (R 2 = 0.53) for the whole of Switzerland, which is mainly composed of alpine ecosystems (60%).…”
Section: Final Predictive Modelsupporting
confidence: 78%
“…Other studies obtained better biodiversity predictions (R 2 > 0.73) under tropical conditions by considering the Shannon index as a dependent variable [43,44]. Under Mediterranean conditions, similar predictions to those obtained in our study were obtained by Simonson et al [45] and Bacaro et al [46] by using the Shannon index and richness, respectively. In another context, Camathias et al [41] obtained lower richness prediction accuracies (R 2 = 0.53) for the whole of Switzerland, which is mainly composed of alpine ecosystems (60%).…”
Section: Final Predictive Modelsupporting
confidence: 78%
“…However, few studies have explicitly analyzed the relationships between plant species diversity and LiDAR measurements [16,17]. Here, we evaluated the potential of LiDAR to map the spatial distribution of species richness in a tropical dry forest based on two main factors related to diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that LiDAR (light detection and ranging) can be a powerful predictor of different vegetation attributes, such as height, basal area, stem density and other vegetation structure parameters [13][14][15]; yet, LiDAR has been used only rarely to estimate plant species diversity [16,17]. This sensor uses laser pulses to directly measure ground and vegetation height, as well as the vertical distribution of intercepted surfaces, making it an ideal tool for mapping vegetation structure with no saturation at high biomass values [18].…”
Section: Introductionmentioning
confidence: 99%
“…New airborne remote sensing technologies, especially LiDAR (Light Detection and Ranging), and physical modeling approaches, such as 4-SCALE [49], ACRM (Two-Layer Canopy Reflectance Model) [50], FRT (Forest Reflectance and Transmittance) [51] and PROSPECT-DART (Discrete Anisotropic Radiative Transfer) [52], have been developed. LiDAR is an active remote sensing technology, and its scanners can emit a high-frequency pulse that can penetrate vegetation canopy gaps and, by recording the return time and intensity of backscatter from targets, provide detailed information of both the ground and multiple points within the forest canopy [53][54][55]. LiDAR has shown enormous potential for capturing canopy structural characteristics, especially in the retrieval of leaf area index (LAI) and tree height, as well as the isolation of individual tree crowns [53,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%